Confederate general of the West : Henry Hopkins Sibley - Thompson, Jerry D. (College Station : Texas A & M University Press, 1996)
Had Henry Hopkins Sibley and his troops succeeded in taking New Mexico, author Jerry Thompson argues, "the entire history of the Southern Confederacy might have been radically altered." In Confederate General of the West, Thompson portrays the life and career of a soldier whose character flaws and leadership weaknesses stood in stark contrast to his sometime military successes and mechanical ingenuity. Civil War scholars, students, and enthusiasts will welcome this new paperback edition of Sibley's biography. As the Utah Historical Quarterly noted after the book first appeared in 1987, Jerry Thompson's scholarship "has provided us with a view of nineteenth-century American military life that rarely surfaces - a comprehensive picture of the mediocre, inept officer who, when thrust into positions of great pressure and responsibility, unwittingly produces great carnage.... Perhaps the greatest value of the book is the extent to which it illustrates the impact of frontier isolation ... on the contentious behavior of the army's officer corps during the antebellum period."
From Natchitoches to West Point -- In the land of alligators and watersnakes -- To the valley of Mexico -- The Texas frontier -- Bleeding Kansas: that turbulent land -- To the Valley of the Saints -- On the trail of the Navajo -- Westward the Texans -- Bloody Valverde -- Glorieta and retreat -- Failure in the bayou country -- In the land of the ancient pharaohs -- By the banks of the Rappahannock.
Originally published: Henry Hopkins Sibley. Natchitoches, La. : Northwestern State University Press, 1987.
Includes bibliographical references (pages 371-385) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Sibley, Henry Hopkins, -- 1816-1886.; Confederate States of America. -- Army -- Biography; Sibley, Henry Hopkins, -- 1816-1886; Confederate States of America. -- Army; Generals -- Confederate States of America -- Biography; New Mexico -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Campaigns; Généraux -- États confédérés d'Amérique -- Biographies; Nouveau-Mexique -- Histoire -- 1861-1865 (Guerre de Sécession) -- Campagnes et batailles; États-Unis -- Histoire -- 1861-1865 (Guerre de Sécession) -- Campagnes et batailles; United States -- History -- Civil War, 1861-1865 -- Campaigns; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY; Generals; Military campaigns; New Mexico; United States; United States -- Confederate States of America; Regions & Countries - Americas; History & Archaeology; United States - General; 1861-1865; Confederate States of America -- Army -- Biography; Generals -- Confederate States of America -- Biography; New Mexico -- History -- Civil War, 1861-1865 -- Campaigns; Sibley, Henry Hopkins -- 1816-1886; United States -- History -- Civil War, 1861-1865 -- Campaigns; Biographies; History